Kepemimpinan Transformasional Pendidikan Berbasis Total Quality Manajement (TQM) - Bukhari, Ahmad (Dinamika Ilmu: Jurnal Pendidikan, 2012)
Field of Education can be said as a field to the change of character, attitude based on moral values such as independence, justice, and humanity and it is not based on any negative emotion such as greed, jealousy, and hate. Leadership is one of the important factors to determine the implementation of education properly. In order to have those moral values in educational institution, concept of transformational leadership is necessary to implement. This concept emphasizes on the importance of a leader to have vision and environment which motivates his/her staff to get achievement beyond the expectation. If it is done properly, educational institution will at least achieve the success referring to the quality indicators; 1) Secured and regulated environment of educational institution 2) The institution has strong leadership mission, 3) There is a strong expectation to get achievement from all the stake holders, 4) There is ongoing human resources development, 5) There is an intensive communication and support from the society.